2020
DOI: 10.1038/s41467-020-15121-2
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of contextual fear memory in hippocampal–amygdala circuit

Abstract: In contextual fear conditioning, experimental subjects learn to associate a neutral context with an aversive stimulus and display fear responses to a context that predicts danger. Although the hippocampal-amygdala pathway has been implicated in the retrieval of contextual fear memory, the mechanism by which fear memory is encoded in this circuit has not been investigated. Here, we show that activity in the ventral CA1 (vCA1) hippocampal projections to the basal amygdala (BA), paired with aversive stimuli, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
150
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(154 citation statements)
references
References 48 publications
4
150
0
Order By: Relevance
“…This result was somewhat surprising given the role of the ventral hippocampus in fear and anxiety and its strong connectivity with subcortical regions that are involved in emotion (Jimenez et al 2018;Hoover and Vertes 2007;Swanson 2006, 2007). However, a recent study found that vCA1 neurons activated during exploration are the same cells that increase their connectivity with basal amygdala neurons after the environment is paired with shock (Kim and Cho 2020). Together with the current results, these data suggest that the ventral hippocampus may primarily transmit context information to the amygdala during fear conditioning.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This result was somewhat surprising given the role of the ventral hippocampus in fear and anxiety and its strong connectivity with subcortical regions that are involved in emotion (Jimenez et al 2018;Hoover and Vertes 2007;Swanson 2006, 2007). However, a recent study found that vCA1 neurons activated during exploration are the same cells that increase their connectivity with basal amygdala neurons after the environment is paired with shock (Kim and Cho 2020). Together with the current results, these data suggest that the ventral hippocampus may primarily transmit context information to the amygdala during fear conditioning.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, our behavioral effects may be small because we did not selectively stimulate vCA1 neurons that were activated during training. These "engram cells" were recently shown to increase their connectivity with BA neurons after context fear conditioning (Kim and Cho 2020). It is possible, therefore, that low-frequency stimulation of vCA1 "engram cells" would enhance freezing after training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sections were then incubated overnight at 4 °C in rabbit polyclonal anti-c-Fos primary antibody (1:2000, #226003, Synaptic Systems) diluted in blocking solution. This antibody is widely used and highly specific for c-Fos protein (Zhou et al, 2019;Kim and Cho, 2020). On the following day, sections were rinsed in 0.1 M TB (3 x 5 minutes) and incubated in biotinylated goat anti-rabbit secondary antibody (1:500, Vector) diluted in Tris B for 2 hours.…”
Section: C-fos Immunoreactivitymentioning
confidence: 99%
“…In normal conditions, that processing leads to a double association that assigns a predictive value to both the context and the cues. Prevailing models postulate that context-US association involves context encoding circuits centered in the hippocampus which send contextual representation to the amygdala where the association takes place (W. Bin Kim & Cho, 2020;Maren et al, 2013), and locate cue-US association in the amygdala (Bocchio et al, 2017). Particularly, solid evidence indicates that tone-US association takes place in cortical and thalamic auditory inputs to the lateral amygdala (Nabavi et al, 2014;Rumpel et al, 2005;Sah et al, 2008).…”
Section: Cued Memory and The Lhbmentioning
confidence: 99%